Fluid Inclusion Raman Spectrometry and Geological Implications of the Lala Copper Deposit in Sichuan - Bo Li; Hui Tang; Liping Luo; Liang Chen; Jin Wu (Kuangchan zonghe liyong, 2023)
In this paper, through the Raman spectroscopy analysis of fluid inclusions in Lala copper deposit, it is found that the types of fluid inclusions are diverse, including not only single pure gas phase or pure liquid phase, gas-rich phase, liquid-rich phase, and many daughter crystals, but also melt-fluid inclusions. The gas phase components of fluid inclusions are not limited to the CO2, but also include N2, CH4 or a mixture of the three. Not only halide daughter crystals but also calcite and hematite daughter crystals are found in fluid inclusion daughter minerals. In conclusion, the Raman spectroscopy characteristics of fluid inclusions show that the ore-forming fluids of the Lala copper deposit have the characteristics of multiple stages and complex sources.